2017
DOI: 10.5114/aoms.2015.50784
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio as a possible indicator of epicardial adipose tissue in patients undergoing hemodialysis

Abstract: IntroductionChronic inflammation is a major risk factor in the pathogenesis of cardiovascular disease in end-stage renal disease (ESRD) patients. Epicardial adipose tissue (EAT) is the true visceral fat depot of the heart. The relationship between coronary artery disease and EAT was shown in healthy subjects and ESRD patients. In the present study we aimed to investigate the relationship between EAT and inflammation parameters including neutrophil-to-lymphocyte ratio (NLR) in hemodialysis (HD) patients.Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…In our study, the optimal NLR cut-off value in distinguishing between patients in Group 1 and patients in Group 2 was ≥ 3.48 and showed a moderate sensitivity (63%) and good specificity (74%). Our results are in agreement with the findings of Sevim et al [20], who found an optimal NLR cutoff value of 3.5 and good sensitivity (76.6%) and low specificity (59.3%) in distinguishing patients with and without AA. Bialas et al [25] investigated the usefulness of the NLR value in the diagnosis of appendicitis in the adult population.…”
Section: Or -Odds Ratio CI -Confidence Interval Wbc -White Blood Cesupporting
confidence: 93%
“…In our study, the optimal NLR cut-off value in distinguishing between patients in Group 1 and patients in Group 2 was ≥ 3.48 and showed a moderate sensitivity (63%) and good specificity (74%). Our results are in agreement with the findings of Sevim et al [20], who found an optimal NLR cutoff value of 3.5 and good sensitivity (76.6%) and low specificity (59.3%) in distinguishing patients with and without AA. Bialas et al [25] investigated the usefulness of the NLR value in the diagnosis of appendicitis in the adult population.…”
Section: Or -Odds Ratio CI -Confidence Interval Wbc -White Blood Cesupporting
confidence: 93%
“…Considering the number and the heterogeneity of RCC prognostic factors and the interactions between renal cell carcinoma and immune cells, searching for widely available and reliable inflammatory biomarkers seems essential [7,9]. Up to now, numerous studies have reported that some non-specific indicators derived from complete blood count (CBC) give added prognostic value in the assessment of various diseases, including renal cell carcinoma [10][11][12][13][14][15][16]. Amongst the most promising indices that are based on absolute values of circulating inflammatory cells, platelet-lymphocyte ratio (PLR), neutrophil-lymphocyte ratio (NLR), derived neutrophil-lymphocyte ratio (dNLR) and lymphocyte-monocyte ratio (LMR) are being particularly deeply investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil-to-lymphocyte ratio (NLR) increases with increasing severity of inflammatory response and has been associated with poor patient outcomes in cancers (Grenader et al 2016 ; Ojerholm et al 2017 ), cardiovascular diseases (Kurtul et al 2016 ; Sari et al 2015 ), ischemic diseases (Aktimur et al 2016 ; Qun et al 2017 ), and a variety of other conditions (Ozcicek et al 2017 ; Pan et al 2017 ; Senturk et al 2016 ). A recent study from this research group (Wang et al 2016 ) showed an association of high NLR with 30-day mortality in ICH patients.…”
Section: Introductionmentioning
confidence: 99%